Bringing Awareness to the Barriers Causing the Lack of Parent Involvement in the Public Schools - Billie Laminta Poe (Adult Education Research Conference, 2015)
The primary purpose of this study was to bring awareness to barriers that are causing the lack of parent involvement in public schools. Data were collected from parents, teachers, principal, one focus group, field notes and observations, which revealed four concepts: work, communication, student’s academics and strategies promoting parent involvement.
Keywords: parent; school; resistance; barriers